The Impacts of HRM Practices, Work Engagement and Intrinsic Motivation on Turnover Intention: Literature Review - Rashidah, Mohamad Ibrahim; Jarwan Ayman, Mousa Ali (2020)
In the hospitality industry, employee turnover is extremely high which attracts both researchers and hoteliers to discover the reasons for this phenomenon due to the incredibly negative impacts of employee turnover on the hospitality industry's success, stability, and growth. However, prior studies had highlighted the great impacts of human resource management practices, work engagement and employee intrinsic motivation on employee turnover intention but these studies had theoretically and empirically investigated the influences of these factors on employee turnover intention separately leaving significant research gaps. The present paper aims to investigate these constructs theoretically in one model. Also, the current paper has highlighted some critical research gap in the literature of human resource management practices, work engagement, intrinsic motivation, and turnover intention, as well as it has theoretically filled these gaps.